Capturing and Quantifying Tactical Behaviors in Small-Sided and Conditioned Games in Soccer: A Systematic Review. Issue 1 (2nd January 2022) - Coito, Nuno; Davids, Keith; Folgado, Hugo; Bento, Teresa; Travassos, Bruno
ABSTRACT: Purpose : To systematically describe and analyze the tracking systems, the variables, and the statistical methods used to evaluate the players and teams' tactical behavior in small-sided and conditioned games (SSCGs). Methods : A search was done in Web of Science, PubMed, Science Direct, and Scielo databases to identify manuscripts published between 2008 and 2019 that manipulated small-sided and conditioned games (SSCGs) and analyzed tactical behaviors of players and teams. Results : From 349 articles identified, 31 were selected for review. To collect positional data, the global positioning system (GPS), the local position measurement (LPM) system, and TACTO were identified as reliable tracking systems. Twenty-one positional variables were identified to evaluate tactical behaviors, grouped into five main categories: team balance, playing space, width and length of playing space, and interpersonal distance. Tactical behavior patterns were analyzed using approximate entropy, sample entropy, Shannon entropy, and patterns of coordination between players and teams were analyzed using relative phase and running correlation. Discussion : The tracking systems analyzed were reliable but revealed different advantages and disadvantages of their use. Authors should define the use of each tracking system based on their purpose and level of precision required for analysis. A great duplication was observed on the variables used with similar purposes of tactical analysis. The identification of the variables according to their purpose of analysis will allow a better understanding of their use in the future.